Case report: Blindness associated with Learedius learedi trematode infection in a green sea turtle, Chelonia mydas, of the northern Red Sea - Morick, Danny; Bachmann, Vanessa M.; Shemesh, Eli; Botero-Anug, Ana Maria; Zemach-Shamir, Ziv; Aizenberg, Zahi; Davidovich, Nadav; Goldberg, Daphne W.; Kan, Gaston; Ofri, Ron; Tchernov, Dan; Levy, Yaniv (Frontiers in Veterinary Science, 2023)
Spirorchiid blood flukes are widespread in sea turtles, causing disease and mortality in their populations, with high prevalence in several ocean basins. Besides being leading parasitic causes of sea turtle strandings in several parts of the world, these infectious agents can cause endocarditis, vasculitis, thrombosis, miliary egg granulomas, and aneurysms, which ultimately may compromise the survival of green sea turtles. More severe cases may also result in multifocal granulomatous meningitis or pneumonia, both of which can be fatal. Herein, we report the first case of severe trematode infection, Caused by Learedius learedi, in a green sea turtle in the northern Red Sea; this infection is associated with bilateral blindness. Necropsy revealed multiple granulomas with intralesional trematode eggs in the optic nerve, eyes, spleen, heart, and lungs. The parasite was identified as Learedius learedi through specific primers of the ribosomal genome and COI sequences obtained from GenBank. Altogether, these findings emphasize the importance of recognizing the systemic nature of this particular fluke infection to ultimately protect the lives of these marine animals and ensure the sustainability of these species in the wild.